Nonsurgical Management of Oral Mucocele by Intralesional Corticosteroid Therapy - Rupam Sinha; Soumyabrata Sarkar; Tanya Khaitan; Arpita Kabiraj; Anirban Maji (International Journal of Dentistry)
Background. Oral mucocele is a common lesion resulting from an alteration of minor salivary glands due to mucus accumulation. Rapid appearance, specific location, history of trauma, bluish colour, and consistency help in the diagnosis. Conventional surgical removal is the treatment of choice but has several disadvantages like damage to adjacent ducts with further development of satellite lesions. Therefore, the present study was undertaken to evaluate the efficacy of intralesional corticosteroid injection (betamethasone) as a nonsurgical treatment procedure in oral mucoceles. Material and Method. A total of 20 cases (males and females, 10–30 years of age) with clinically diagnosed oral mucoceles were given 1 mL of betamethasone intralesionally. All the patients were examined after a period of 7, 14, and 21 days to evaluate the response of the lesion towards treatment and consequently given the 2nd, 3rd, 4th injections. If the lesion resolved after one or two injections, the treatment was discontinued. Results. Out of the 20 cases, 18 of them showed complete regression of the lesion whereas the remaining 2 cases showed decrease in size. All the patients received maximum of 4 consecutive shots in weekly interval. Conclusion. Intralesional corticosteroid therapy can be considered as the first choice in the treatment of oral mucoceles.